An Adult Case of Primary Rhabdomyosarcoma of the Trachea with Resection of Seven Cartilage Rings and Primary Reconstruction - Miwa, Ken; Taniguchi, Yuji; Nakamura, Hiroshige (The Thoracic and Cardiovascular Surgeon, 2012)
A 74-year-old female consulted a local clinic with bloody sputum and dyspnea. Bronchoscopy revealed a tumor with ∼80% stenosis in the trachea. She was referred to our hospital. Biopsy findings suggested primary rhabdomyosarcoma of the trachea. Cervical computed tomography (CT) revealed a tumor involving the 3rd to 9th tracheal cartilages. Tubular resection of the 3rd to 9th tracheal cartilages and tracheal reconstruction were performed. Finally, a pathological diagnosis of rhabdomyosarcoma was made. Primary rhabdomyosarcoma of the trachea is extremely rare.
Keywords: tracheal tumor; rhabdomyosarcoma; trachea